Faktor-Faktor Yang Mempengaruhi Kurangnya Kesadaran Masyarakat Dalam Berkurban - Dahliati Simanjuntak (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2019)
The people of the prophet Muhammad SAW. required to sacrifice. To remind the blessings that Allah gave to the prophet Ibrahim for being obedient and obedient to Allah and to draw closer to Allah SWT. Allah SWT prescribed the qurban worship to revive the prophet Abraham's blessing and make rizqi spaciousness for humans on the Eid al-Adha feast day. Today, during the Eid al-Adha feast, there are still some villages where there is absolutely no qurban implementation, because local people do not know the implementation of qurban law, do not know the benefits and wisdom of the qurban, consider the qurban is only focused on one person who issues the qurban, and consider the sacrifice is only limited to worship to get the reward, there are many other ways to be able to get the reward in addition to issuing qurban, which causes awareness in the community is very minimal to sacrifice, so that no qurban implementation is found on the Eid al-Adha feast day.